Prevalence of Thyroid Disorders in Patients Visiting a Tertiary Care Center in New Delhi: A Three-Year Study - Tayal, Devika; Goswami, Binita; Gupta, Nikhil; Chawla, Ranjna; Gupta, Vinod Kumar; Singh, Bipin; Chawla, Aparna (Asian Journal of Medical Sciences, 2013)
Background: Thyroid disorders constitute the most prevalent endocrine disorder in our country. Thyroid disorders are classified broadly as hyperthyroidism and hypothyroidism depending on the functional capacity of the thyroid gland. These two entities are further segregated as sub clinical and overt dysfunction. The present study attempts to evaluate the prevalence of thyroid disorders in north Indian population which is more prone to hypothyroidism due to iodine deficiency observed in the Himalayan belt. Materials and Methods: A total of 7474 patients presenting to the department of Biochemistry, G B Pant hospital, Delhi, were enrolled in the study. The patients were examined and asked to report after overnight fast for sample collection on a prescribed date. Thyroid hormone estimation was done with commercially available ELISA kits supplied by Cal biotech, USA. Statistical Analysis was done using Microsoft Office “Excel” with Windows 2007 Operating System and multiple comparisons were made using SPSS 12.0 statistical software package. Results: The majority of the patients (approximately 85%) were Euthyroid. Only 1.22% of the total number of referred patients turned out to be hyperthyroid. Hypothyroidism was more prevalent with the number of patients diagnosed with both sub clinical and overt hypothyroidism being 987 (13.2%). Conclusions: We have strived to provide a baseline orientation regarding the prevalence of thyroid disorders in the representative north Indian population in the post iodine fortification era. DOI: http://dx.doi.org/10.3126/ajms.v3i4.7705 Asian Journal of Medical Science Vol.3(4) 2012 pp.15-23